2013
DOI: 10.1007/978-3-319-02850-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Electronic and Dielectric Properties of Molybdenum Disulfide

Abstract: We report tunability in electronic and dielectric properties of a technologically promising nanomaterial MoS 2 . The properties of MoS 2 can be tuned by varying the layer thickness, by applying mechanic strain, by tuning the interlayer distance, and by applying external electric field. Reducing the slab thickness systematically from bulk to monolayers causes blue shift in the band gap energies, thereby, resulting in tunability of the electronic band gap. By reducing the number of layers from bulk to monolayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 96 publications
1
10
1
Order By: Relevance
“…It can be found that the band structures adjacent to the band gap of un-doped monolayer MoS 2 calculated by GGA and GGA+U methods are mainly dominated by the hybridization of Mo 4d and S 3p orbitals, which is consistent with previous calculated results [17][18]. The Brillouin-zone of the monolayer MoS 2 was performed over the 7×7×1 k-point grids using the Monkorst-Pack method, where the self-consistent convergence of the total energy is 1.0×10 -5 eV/atom.…”
Section: Methodssupporting
confidence: 91%
“…It can be found that the band structures adjacent to the band gap of un-doped monolayer MoS 2 calculated by GGA and GGA+U methods are mainly dominated by the hybridization of Mo 4d and S 3p orbitals, which is consistent with previous calculated results [17][18]. The Brillouin-zone of the monolayer MoS 2 was performed over the 7×7×1 k-point grids using the Monkorst-Pack method, where the self-consistent convergence of the total energy is 1.0×10 -5 eV/atom.…”
Section: Methodssupporting
confidence: 91%
“…The large piezoresistive effects in semiconductors demanded a fundamental theory of the physics. Strain in a crystalline solid modifies the lattice constants and reduces the crystal symmetry, leading to significant shifts in the (2.5) = E energy band edges [62]. The existing theories were based on the change in energy band structure (including band warping and splitting) [63].…”
Section: Piezoresistive Effectmentioning
confidence: 99%
“…The study of exciton based quantum dynamical processes is important as excitonic interactions underlie the unique optoelectronic properties 5,[15][16][17][18] of monolayer dichalcogenides. Several applications [19][20][21][22][23][24] can be linked to the rich many-body effects of excitons in low-dimensional transition metal dichalcogenides.…”
Section: Introductionmentioning
confidence: 99%